Dispersion of deep-sea hydrothermal plumes at the Endeavour Segment of the Juan de Fuca Ridge: a multiscale numerical study - Xu, Guangyu; German, Christopher R. (Frontiers in Marine Science, 2023)
A multiscale numerical framework has been developed to investigate the dispersion of deep-sea hydrothermal plumes that originate from the Endeavour Segment of the Juan de Fuca Ridge located in the Northeast Pacific. The analysis of simulation outputs presented in this study provides insights into the influences of tidal forcing and the buoyancy flux associated with hydrothermal venting on ocean circulation and plume dispersion in the presence of pronounced seafloor topography. The results indicate that tidal forcing drives anti-cyclonic circulation near the ridge-axis, while hydrothermal venting induces cyclonic circulation around vent fields within the axial rift valley. Tidal forcing has a notable impact on plume dispersion, particularly near the large topographic features to the north of the Endeavour Segment. Furthermore, plume dispersion exhibits notable inter-annual variability, with a northbound trajectory in 2016 and a southbound trajectory in 2021. The study also reveals that both buoyancy fluxes and tidal forcing enhance the mixing of hydrothermal plumes with ambient seawater.